ANALISIS DAYA SERAP AIR DAN KEKUATAN BENDING KOMPOSIT SERBUK LIMBAH GERGAJI KAYU INDUSTRI JUKUNG - Saputra, Andrian; Seprianto, Dicky; Mulyadi (AUSTENIT, 2024)
The purpose of the study was to determine the parameters of water absorption and bending strength, with variations in mesh size and volume of sawdust. The powder particles used were 20 mesh and 80 mesh with 70% and 80% wood powder volume variations. Bending test specimens were made using ASTM D790-02 standard and water absorption using SNI 03-2105-2006 standard. The Water Absorbency value is best in specimen BX (70% sawdust, 80 mesh) with a water absorption addition value of 0.43% and the lowest value in variation AY (80% sawdust, 20 mesh) of 0.76%. From the Anova test results, the value of Fhitung mesh size and Fhitug volume of sawdust Fhitung ˃ Ftabel = (Ha) which means it has an effect. Water absorption is influenced by mesh size by 35.59% and wood powder volume by 59.88%.The highest flexural strength value in specimen BX (70% sawdust, 80 mesh) with a flexural strength value of 59.34 MPa and the lowest value in variation BY (80% sawdust, 80 mesh) of 33.37 MPa. From the Anova test results, the value of Fhitung wood powder volume Fhitung ˃ Ftabel = (Ha) which means it has an effect. While the mesh size is Fhitung < Ftabel = (H0) which means there is un effect. Flexural strength is influenced by mesh size by 2.60% and wood powder volume by 83.05%.